Market Orientation Strategies to Improve Marketing Performance: An In-Depth Analysis of Marketing Approaches - Fakhri Naufal Ramadhan; Ferdinand, Augusty Tae (Proceeding of International Management Conference and Progressive Papers, 2024)
The main focus in this study is to use marketing innovation as a mediating variable for the effect of market orientation on marketing performance. This research was analyzed using AMOS 26 on 249 respondents. This model uses 2 additional variables, namely network capability and marketing agility. However, the results show that pro-growth marketing innovation does not show a strong mediating role in this analysis. So that both network capability and marketing agility variables contribute importantly to the development of this marketing.